1998
DOI: 10.1177/0730888498025001005
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Job Characteristics on Active Effort at Work

Abstract: Building on previous research on worker extra-role effort, the authors focus their analysis on the correlates of one subset of behaviors that they call active effort. The authors argue for an exchange model, with organizations offering intrinsic, social, and material inducements in exchange for active effort by workers. Using data from a telephone survey of 270 employed adults in a large midwestern metropolitan area, the authors test a model that measures a variety of structural variables to see how they affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…This study emphasised structural factors, namely social exchange within an social embeddedness perspective. These factors are relatively observable and enduring, and management can decide to modify their employment practices to change the context that is causing the outcomes of interest (Walsh and Tseng, 1998). At a practical level, these results suggest that different types of social embeddedness could be a powerful instrument to encourage both compliance and contextual performance, such as facilitation of network development by junior staff.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This study emphasised structural factors, namely social exchange within an social embeddedness perspective. These factors are relatively observable and enduring, and management can decide to modify their employment practices to change the context that is causing the outcomes of interest (Walsh and Tseng, 1998). At a practical level, these results suggest that different types of social embeddedness could be a powerful instrument to encourage both compliance and contextual performance, such as facilitation of network development by junior staff.…”
Section: Discussionmentioning
confidence: 92%
“…However, we did not test for individu al differences in propensity, competences or preferences to put in more effort in both compliance and contextual performance. Thus, perhaps some of the unexplained variance in the tested models may be due to, for instance, personality characteristics or competences affecting the willingness to engage in efforts to perform well (Walsh and Tseng, 1998). Future resea rch might improve insight s into the nature of these relationships, by adding individual linked variables to explain the relative contribution of individual variables and social embeddedness on efforts to perform well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Job-level practices are important for defining the nature and meaning of work and for influencing the satisfaction or alienation that workers experience in their daily lives (Appelbaum and Batt 1994;Blauner 1964). Organizational-level practices are important for determining the viability of the organization and the level of employee commitment to the organization and its goals (Kalleberg et al 1996;Walsh and Tseng 1998).…”
Section: The Organization Of Work and Workplace Practicesmentioning
confidence: 99%
“…Several empirical studies show a positive relationship between specific human-resource practices, and employee effort (Gilley, Gilley, Jackson & Lawrence, 2015). Walsh and Tseng (1998) have showed that employees' participation has a positive effect on their effort. Den Hartog and Verburg (2004) have found positive relationships between a set of practices labeled "employee skills and direction, " involving strict selection, an emphasis on employee development and internal promotions, and having an overarching philosophy in terms of a mission statement and HR strategy as well as employee willingness to go beyond contract.…”
Section: Mediating Role Of Effort In the Relationship Between Hpws Anmentioning
confidence: 99%